Connecting the Dots: The Early Impacts of Increased Paid Maternity Leave on Child Development - Catherine Haeck (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2015)
This paper evaluates the effect of extended maternal care on children's development at age 4 and 5 using observational data prior to and after the Canadian parental leave reform, which extended total paid leave from 25 to 50 weeks. In contrast with previous research on the Canadian parental leave reform, we estimate the impact of the reform while controlling for underlying trends in the outcome variables. We find that the policy change had positive effects on the cognitive development of children as well as parent-reported measures of child health and family well-being. Effects on behavioral development are mainly not significant. These results must be interpreted with respect to the effective treatment period and the type of care displaced. We find that mothers increased their time at home from 7 to 11 months and that the type of care displaced was mainly unregulated and provided by individuals without specific training.
Keywords: J13; J18; J22; J24; 330; maternity leave reform; child development; family well-being; natural experiment